Upaya Meningkatkan Kapasitas UMKM Melalui Pelatihan Manajemen Laporan Keuangan dan Bisnis (Business Plan) - Denny Kurniawan; Sastya Putri (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The Community Service activity, themed “Efforts to Increase the Capacity of MSMEs thru Financial and Business Management Training (Business Plan),” was attanded by 33 MSME participants from the East Lampung District Cooperative and MSME Service. Based on the Q&A session, participants asked many questions and consulted about the material presented, indicating that the activity was very beneficial for them. Participants questions related to a simple financial reporting process, both written and thru applications, and how to create a business plan to calculate the cost of developing MSMEs. It is hoped that this service activity can continue to expand existing MSMEs in East Lampung.